2020
DOI: 10.1186/s12301-020-00061-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxidative stress on semen parameters in normozoospermic infertile men: a case–control study

Abstract: Background Oxidative stress has been implicated in male infertility through decrease in sperm quality. However, men with normal semen parameters (normozoospermia) may be unable to fertilize their partners even when they have normal sperm function. Thus, they would be considered infertile. The purpose of this study was to investigate the role of oxidative stress in the pathogenesis of unexplained male infertility. Methods In this case–control study, infertile men with normozoospermia (n = 46) and fertile cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The non-significant differences observed in sperm volume and pH of the control subjects compared against the infertile subjects with bacterial infection (Table 2) is in line with the findings of Palani & Alahmar [22]. They also reported no significant difference in the ejaculatory volume of semen of bacterial-infected infertile males and control.…”
Section: One-way Anova Of Seminal Plasma Proteins Anti-oxidants Enzym...supporting
confidence: 86%
“…The non-significant differences observed in sperm volume and pH of the control subjects compared against the infertile subjects with bacterial infection (Table 2) is in line with the findings of Palani & Alahmar [22]. They also reported no significant difference in the ejaculatory volume of semen of bacterial-infected infertile males and control.…”
Section: One-way Anova Of Seminal Plasma Proteins Anti-oxidants Enzym...supporting
confidence: 86%
“…Adequate levels of reactive oxygen species (ROS) maintain the normal function of sperm [ 7 ], but ROS overproduction depletes the levels of antioxidants, increases oxidative stress, damages the structure and quality of sperm cells, and consequently causes infertility [ 8 , 9 ]. In addition, lower total antioxidant activities [ 10 ] and higher levels of ROS [ 11 ] have been identified in semen from infertile men compared with that from fertile men.…”
Section: Introductionmentioning
confidence: 99%
“…In nearly 25% of male infertility cases, men have demonstrated normal sperm parameters but are still unable to father a child, which is termed unexplained infertility. 51,52 A recent Indian study reported 33.33% men with unexplained infertility. 53 Microbiological analysis of infertile couples (n = 285) with normal sperm count/ motility showed that 46.3% presented with an asymptomatic genital tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…The study highlights that the males with genital infection/inflammation showed lower SP‐D levels, possibly due to their engagement at the site of infection, enhanced elastase levels and altered T/E ratio. In nearly 25% of male infertility cases, men have demonstrated normal sperm parameters but are still unable to father a child, which is termed unexplained infertility 51,52 . A recent Indian study reported 33.33% men with unexplained infertility 53 .…”
Section: Discussionmentioning
confidence: 99%